Enhanced catalytic activity with high thermal stability based on multiple Au cores in the interior of mesoporous Si–Al shells. Issue 60 (2nd July 2015) - Zhang, Yiwei; Xiang, Sanming; Zhou, Yuming; Xu, Yuanmei; Zhang, Zewu; Sheng, Xiaoli; Wang, Qianli; Zhang, Chao
<x xml:space="preserve">Abstract</x> Mesoporous Si–Al/Au nanocatalysts were synthesized by combining the advantage of good permeability from mesoporous Si–Al shells and the high activity upon multiple Au cores.